Teaching is More than Applying Knowledge: Developmental tasks of pre-primary and primary teachers and effects on teacher education - Manuela Keller-Schneider (Charles University, 2020)
Teaching is a challenging job, due to the changing requirements of changing times. Routine as a teacher is not possible. Student teachers need to be prepared to deal with challenging situations. The perception of requirements as challenges and problem-solving capacities are needed to master the job as a teacher. This article explains why problem-solving capacities are essential for teacher professionalization, what requirements challenge beginning teachers most, and how teacher education can foster student teachers to be prepared to deal with challenges of the first stage of their career. Based on the model of professionalization in which individual resources play a crucial role in the perception of challenge and the coping with it, results from a study on the challenges of beginning teachers were shown. The main finding that beginning teachers are most challenged by teaching that refers to individual students' needs leads to consequences for teacher education. Student teachers need to build up adaptive knowledge for school and reflection competences. Explanations on a course at Zurich University of Teacher Education show how student teachers are educated in a problem-based setting to build up knowledge and competence that are useful in order to teach considering individual students' needs. The article closes with a model of reflection on challenging situations that takes into account different factors of individual resources that are relevant for professionalization. Keywords: teacher education, developmental tasks, requirement appraisal, individual resources, reflection, problem-based learning